Socio-health factors, ability to perform instrumental and basic activities of daily living, and use of assistive mobility devices during the COVID-19 pandemic: Interrelationships and impact on long-term survival - Vicente Martín Moreno; María Inmaculada Martínez Sanz; Irene Sánchez González; Miguel Recuero Vázquez; Sara Guerra Maroto; Miriam Fernández Gallardo; Amanda Martín Fernández; Julia Herranz Hernando; María Palma Benítez Calderón; Elena Pérez Rico; Laura Calderón Jiménez; Elena Sánchez Rodríguez; et al. (PLoS ONE, 2025)
Introduction Functional dependence for the performance of basic activities of daily living (ADLs) is one of the main causes of institutionalization. This study analyzed the interrelationships between basic and instrumental activities of daily living, use of assistive mobility devices, socioeconomic factors, changes during COVID-19 pandemic confinement, and 3-year survival in the ADL-dependent people of the Orcasitas neighborhood of Madrid (Spain). Methods A longitudinal descriptive study, carried out on the entire population of functional dependent patients (Barthel ≤ 60) in the Orcasitas neighborhood. We included 127 patients, 78.7% women and 21.3% men, with a mean age of 86 years. Pre-pandemic, post-confinement (June 2020) and June 2023 data were contrasted. Results Results: The use of crutches-cane was associated with a higher probability of being independent in performing ADLs, leaving home (OR 4.848; CI 1.428–16.458), improving functional capacity during confinement (OR 3.621; CI 1.409–9.308), and even ceasing to be functionally dependent (OR 0.394; CI 0.165–0.941). Using a wheelchair was associated with a higher level of dependency (OR 2.583; CI 1.167–5.714) and higher mortality (HR 1.913; CI 1.106–3.309). After COVID-19 pandemic confinement, having a financial income of less than 11,200 euros/year (OR 2.413; CI 1.159–5.023), or using a wheelchair (OR 2.464; CI 1.009–6.017), increased the risk of living homebound. Living homebound decreased the probability of survival, while maintaining the ability to leave home increased it (OR 3.880; CI 1.834–8.211). Economic capacity modulated the results. Lower economic capacity was associated with higher mortality (HR 2.47 (Exp(B) 0.405; CI 0.232–0.708). Living in confinement and having a low economic income were associated with higher mortality (OR 0.127; CI 0.029–0.562), mortality that was also higher with respect to those who could leave their home (OR 6.697; CI 2.084–21.525). Conclusions Functional ADL-dependence affects multiple facets of the person. Confinement triggered changes in the baseline conditions of this cohort, which were influenced by the level of dependency, mobility capacity and economic income level. Economic capacity modulated the results, showing that social inequalities influence survival. The ability to leave home and the use of a wheelchair should be included in the assessment of the risk level of this population group.